Customer Loyalty Model Through Customer Commitment With Quality Results and E-Sq at Padang Nagari Bank - Susriyanti Susriyanti; Nandan Lima Krisna; Lusiana Lusiana (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to identify and analyze the direct and indirect effects of Quality Results, and Electronic Service Quality on customer loyalty through customer commitment to Bank Nagari. Bank Nagari is one of the regional assets as an embodiment of local wisdom aimed at the development of the West Sumatera region, and it should receive support from the entire community. However, the trend shows fluctuations in customer loyalty. This type of research is associative with a sample of 200 customers drawn through the accidental sampling method. The data analysis model uses SEM PLS. The results of this study are from the seven hypotheses proposed; both direct and indirect effects are overall acceptable. This means that the Quality of Results and Electronic Service Quality have a direct or indirect effect on customer loyalty through customer commitment to Bank Nagari Kota Padang. To get customer loyalty, it can be done by improving the quality of results such as timeliness in services as a customer evaluation of the results of their service activities. In addition, e-service quality banks need to continue to improve quickly, keep pace with technological developments, educate customers smartly and continuously for the use of these electronic services.